Peer-led BASICS intervention to reduce alcohol consumption and alcohol-related consequences among university students: a randomized controlled trial - Lavilla-Gracia, María; Pueyo-Garrigues, María; Calavia Gil, Diego; Esandi-Larramendi, Nuria; Alfaro-Diaz, Cristina; Canga-Armayor, Navidad (Frontiers in Public Health, 2023)
Introduction Alcohol consumption is the main substance abused during university and is associated with physical, legal, emotional, social, and cognitive consequences. The peer-led BASICS intervention has been shown to be effective in decreasing the quantity and frequency of drinking, the estimated peak blood alcohol concentration (BAC), and the number of binge drinking episodes among this population. Objective This study evaluated the effectiveness of the peer-led BASICS intervention to reduce risky alcohol consumption among university students in the Spanish context. Materials and methods A two-arm randomized controlled trial in a university in northern Spain including 308 first- and second-year university students recruited between October 2022 to March 2023. The intervention was a 30-min in-person peer-led motivational interview. Participants were assessed at baseline and 1-month postintervention. The primary outcome was the quantity and frequency of alcohol consumption during a typical week. The intervention effect was verified using a mixed factorial ANOVA model. Results Compared with students in the control group, students who received the intervention reduced the number of drinks per week by 5.7 (95% CI 5.54, 5.86); the number of drinks consumed in a typical weekend by 5.2 (95% CI 5.07, 5.33); the number of drinks consumed on the occasion of greatest consumption by 4.9 (95% CI 4.78, 5.02); the number of binge drinking episodes by 1.4 (95% CI 1.37, 1.43); the peak BAC on a typical week and on the occasion of greatest consumption decreased by 0.06 (95% CI 0.058, 0.062) and 0.09 (95% CI 0.088, 0.092); the number of alcohol-related consequences by 5.8 (95% CI 5.67, 5.93); and the motivation to change their alcohol use increased by −0.8 (95% CI −0.85, −0.75). Conclusion The peer-led BASICS intervention is effective in changing alcohol consumption and its related consequences among Spanish university students in the short term. The action of nursing students as counselors positively impacted drinking patterns among their peers. Clinical trial registration <ext-link ext-link-type="uri" xlink:href="https://clinicaltrials.gov/study/NCT05639374?intr=Effectiveness%20of%20a%20Peer-led%20Program%20to%20Prevent%20Alcohol%20Consumption&rank=1&page=1&limit=10" xmlns:xlink="http://www.w3.org/1999/xlink">https://clinicaltrials.gov/study/NCT05639374?intr=Effectiveness%20of%20a%20Peer-led%20Program%20to%20Prevent%20Alcohol%20Consumption&rank=1&page=1&limit=10, identifier: NCT05639374.